1997
DOI: 10.1002/(sici)1097-0142(19970701)80:1<8::aid-cncr2>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results of the treatment of 23 patients with immunoproliferative small intestinal disease

Abstract: (1 g/day, orally) for a median duration of 7 months (range, 6-11 months) initially, whereas the remaining patients (9 Stage B patients and 7 Stage C patients) received 1 Department of Medical Oncology, Ibn-i Sina combination chemotherapy (cyclophosphamide, vincristine, procarbazine, and Hospital, Ankara University School of Medicine, prednisolone [COPP regimen]) followed by tetracycline at a dose of 1 g/day for 6 Sihhiye-Ankara, Turkey.more months in patients with complete response (CR) after the COPP regimen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 16 publications
0
23
0
6
Order By: Relevance
“…Pharmacologic treatment • Akbulut et al [31] reported 5-year treatment results of 23 Turkish patients with IPSID, including five with secretion of ␣ chains. Seven patients had stage A disease and were treated with tetracycline for a median of 7 months, whereas the remaining 16 patients (nine stage B, seven stage C) received combination chemotherapy (cyclophosphamide, vincristine, procarbazine, and prednisolone).…”
Section: Diet and Lifestylementioning
confidence: 99%
“…Pharmacologic treatment • Akbulut et al [31] reported 5-year treatment results of 23 Turkish patients with IPSID, including five with secretion of ␣ chains. Seven patients had stage A disease and were treated with tetracycline for a median of 7 months, whereas the remaining 16 patients (nine stage B, seven stage C) received combination chemotherapy (cyclophosphamide, vincristine, procarbazine, and prednisolone).…”
Section: Diet and Lifestylementioning
confidence: 99%
“…IPSID has been reported from various parts of the world including India [10,11]. Chronic infection results in constant antigenic stimulation which in the presence of malnutrition and genetic predisposition (HLA B12, HLA A9) results in uncontrolled B cell proliferation [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund der Hypothese, dass ein infektiöses Agens antigener Stimulus der Immunproliferation sein könnte, wird im Stadium A von den meisten Autoren eine antibiotische Therapie mit Tetracyclin, zwischen 1 und 2 g/Tag empfohlen.Im Verlaufe einer solchen Behandlung können Vollremissionen in 33-71% der untersuchten Fälle erreicht werden [2,3,8,12,16].…”
Section: Therapieunclassified
“…Uneinigkeit besteht über die Behandlungsdauer mit Antibiotika,hier schwanken die Angaben zwischen 6 Monaten und 2 Jahren [2,10,16], in Einzelfällen jedoch sogar über insgesamt 5 Jahre [3].…”
Section: Therapieunclassified
See 1 more Smart Citation